2020
DOI: 10.33837/msj.v3i1.1183
|View full text |Cite
|
Sign up to set email alerts
|

Amplification test and selection of markers analogue to resistance genes in species and commercial varieties of Passiflora spp.

Abstract: Brazil is highlighted as the largest producer and consumer of passion fruit (Passiflora) and holder of representative biodiversity. Studies dedicated to the genetic characterization of the genus in order to understand the existing diversity are important for the advancement of genetic improvement and conservation programs. The aim of this study was to select combinations of RGA (Resistance Genes Analogs) primers for commercial passion fruit species and varieties. To this end, amplification tests were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
(25 reference statements)
0
3
0
2
Order By: Relevance
“…These described adequate amplification with 100% polymorphism for Passiflora Spp. (Souza et al, 2020). In Passiflora setácea, they registered polymorphism ranging from 99 to 100% (Pereira, Corrêa, & Oliveira, 2015).…”
Section: Resultsmentioning
confidence: 97%
“…These described adequate amplification with 100% polymorphism for Passiflora Spp. (Souza et al, 2020). In Passiflora setácea, they registered polymorphism ranging from 99 to 100% (Pereira, Corrêa, & Oliveira, 2015).…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, cross-pollination mediated by external agents is required, which contributes to the increase of the genetic variability of these species, for example, in P. cincinnata (Silva et al, 2022). Sousa et al (2020) using 31 ISSR markers in 25 wild passion fruit species and Sousa et al (2015) observed that 20 primers had polymorphic loci. In view of the studies with the same primers in different species of the genus, it was observed that these markers, in addition to enabling molecular studies, also inform the divergence between species, whose characteristic makes this marker a potential tool for the selection of taxa in wild species of Passiflora L.…”
Section: Discussionmentioning
confidence: 99%
“…Para a caracterização da diversidade genética, foram utilizados nove pares de iniciadores RGA previamente selecionados para o gênero Passiflora (Tabela 1) (PAULA et al, 2010;SOUSA et al, 2015). A despeito de comporem a classe dos marcadores dominantes, cuja genotipagem não permite a distinção de alelos (ou seja, a identificação direta de heterozigotos), a heterozigosidade esperada (He) pode ser estimada de forma aproximada considerando a hipótese do EHW.…”
Section: Genotipagem Das Amostrasunclassified
“…Também contribuem para a construção de mapas genéticos, juntamente com outros tipos de marcadores (PEREIRA et al, 2013). Além disso, estudos de avaliação com marcador molecular dessa natureza em diferentes espécies e variedades comerciais de maracujazeiros trazem informações de iniciadores mais adequados e informativos para a caracterização genética (SOUZA et al, 2020).…”
Section: Introductionunclassified